THE IMPORTANCE OF ENVIRONMENTAL EDUCATION IN THE CONSERVATION OF LIFE ON THE GROUND - Ramos, Tatiana; Abrão Inácio, Isabelle; Velozo da Silva, Gleycon (Journal of Interdisciplinary Debates, 2021)
The soil has an innumerable diversity of living beings, whose function is to maintain balance and proper functioning, which is why these beings can be known as bioindicators of soil quality. Thus, this theme becomes very important in environmental education, which in many places addresses this issue through research and teaching projects that aim to encourage people to think more sustainably in relation to the soil and especially the environment. The present work provides a survey of information on the subject and highlights the importance of soil invertebrates.